Pediatric Trapped Fourth Ventricle: The Need for Objective Surgical‐Selection Criteria and Long‐Term Surveillance After Open Fenestration - Muhammad Abdullah Awan; Hammad‐ud‐din Raza (Clinical Case Reports, 2026)
ABSTRACT Open fenestration can be an effective treatment for pediatric trapped fourth ventricle, but case reports should move beyond successful short‐term decompression. Future reports should include objective surgical‐selection criteria, intraoperative confirmation of adhesions, standardized imaging metrics, and long‐term surveillance end points to clarify durability and recurrence risk.